2019
DOI: 10.7759/cureus.4645
|View full text |Cite
|
Sign up to set email alerts
|

A Successful Outcome Despite Delayed Intervention for Cauda Equina Syndrome in a Young Patient with a Posterior Epidural Disc Extrusion

Abstract: Epidural disc extrusion is extremely rare and may cause cauda equina syndrome. This is a surgical emergency and needs rapid decompression. Although cauda equina is commonly caused by disc herniation, this is an unusual presentation with epidural disc extrusion. We present a very rare case of Cauda Equina syndrome, resulting from an epidural disc extrusion at L3-L4 level. Patient care and progress notes were reviewed along with pre-, post-, and intra-operative radiological imaging. Here, a 19-year-old male with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…After the surgery, the patients complained of only incisional pain and he was discharged on postoperative day 3 26 . Douraiswami et al (2016) reported a case of CES caused by disc prolapse.…”
Section: Discussionmentioning
confidence: 99%
“…After the surgery, the patients complained of only incisional pain and he was discharged on postoperative day 3 26 . Douraiswami et al (2016) reported a case of CES caused by disc prolapse.…”
Section: Discussionmentioning
confidence: 99%
“…The first report of "posterior epidural migration of disc" in 1973 by Lombardi [18]. Most patients with posterior epidural sequestrated disc present with bilateral symptoms and different degrees of weakness [2][3][4][5][6][7][8][9][10][11][19][20][21]. Moreover, bowel bladder involvement was not uncommon among patients with posterior epidural sequestrated disc [2-11, 19, 20].…”
Section: Case Presentationmentioning
confidence: 99%
“…Mugge L [19] L3-4, 1 Progressive neurological deficits including bilateral foot drop along with bowel and bladder dysfunction.…”
Section: Case Presentationmentioning
confidence: 99%